The dynamic relationship between response processes and self-regulation in critical thinking assessments. (December 2021) - Hyytinen, Heidi; Ursin, Jani; Silvennoinen, Kaisa; Kleemola, Katri; Toom, Auli
Highlights: The performance task and selected-response questions trigger different processes. The performance task evokes holistic response and self-regulatory processes. Selected-response questions result in fragmented and question-oriented processes. Students' response and self-regulatory processes are intertwined. Variation in self-regulation is associated with the complexity of response processes. Abstract: Our aim was to explore higher education students' response and self-regulatory processes plus the relationship between these, as evidenced in two types of performance-based critical thinking tasks included in the Collegiate Learning Assessment (CLA+) International instrument. The data collection consisted of 20 cognitive laboratories. The data were analyzed using a qualitative approach. The tasks were found to trigger different response and self-regulatory processes. Overall, the performance task evoked more holistic processes than the selected-response questions, in which students' processes were more question-oriented. The results also indicated the entanglement of students' response and self-regulation processes. Three self-regulation groups were identified. Students with versatile self-regulation skills were able to complete the task thoroughly, whereas students with moderate self-regulation skills faced challenges in monitoring and evaluating their performance. Students who were lacking in self-regulation struggled both with the task as a whole and their own progress. Implications for higher education are discussed.